Selective production of aldehydes: From traditional alternatives to alcohols photo-oxidation using g-C3N4-based materials - Quintana, M. A.; Rodriguez-Padron, Daily; Jiménez Calvo, Pablo; Carlero de Hoces, Monica; Solis, Rafael R.; Muñoz-Batista, Mario J. (Materials Advances, 2025)
Once largely overlooked, selective photocatalysis has recently seen rapid development and now includes several new applications. One of the most sought-after applications is the photocatalytic oxidation of alcohols to their corresponding aldehydes. There is significant interest in the selective production of compounds such as benzaldehyde, cinnamaldehyde, and vanillin using this technology, among various other valuable components. This work examines common production methods and alternative synthesis routes for aldehydes from their alcohols, focusing on g-C3N4-based photocatalytic schemes. The discussion includes an analysis of g-C3N4 structures that have shown significant results in the selective oxidation of alcohols and provides a critical review of the mechanism, highlighting the importance of reporting quantum yields of the reaction. Literature data suggest that photocatalysis is a viable alternative to traditional aldehyde production methods, with maximum selectivity values towards the product of interest (>99%), but catalytic activity remains limited, with relatively low quantum yields, restricting the transition beyond the laboratory scale. However, the charge handling in g-C3N4-based advanced materials is adequate for this application, and their implementation under solar illumination conditions is promisin